Resurgence of Fentanyl as a Drug of Abuse - Lauren P Tamburro; Jenan H Al-Hadidi; Ljubisa Jovan Dragovic (Wolters Kluwer Medknow Publications, 2016)
Fentanyl, a powerful opioid analgesic introduced over 50 years ago, has a major role in modern anesthesia and chronic pain relief but has also gained a major role in illicit use. After a spike in fentanyl abuse between 2005 and 2007, fentanyl deaths decreased until 2010, with the introduction of "abuse-deterrent" OxyContin. Our data indicate a recent rise in fentanyl-related deaths beginning in 2013, which follows national trends. With the re-emergence of the synthetic narcotic analgesic of high potency as a popular drug of abuse and the alarmingly increasing mortality associated with its abuse, there are profound implications for public health, health care providers, law enforcement, and the society in general.